The rain forest counts! - McCourt, Lisa.; Nathan, Cheryl, 1958- ([U.S.] : BridgeWater Books, 1997)
"Introduces a variety of rain forest animals while counting from one up to ten and then back down to one again."
Keywords: Rain forest animals -- Fiction; Counting; Stories in rhyme